Struvite 결정화 반응을 이용한 침출수 내 고농도 암모니아성 질소의 처리 특성 - 김수진; 김진수; 이지영; 강민구; 이상일 (한국수처리학회지, 24(6), 2016)
This study was focused on the removal of high concentration ammonia nitrogen in landfill leachate by using struvite crystallization. Struvite crystallization showed high removal efficiency of ammonia nitrogen and phosphate in landfill leachate. Therefore, this study was evaluated to optimum conditions by pH, mole ratio, dosage of seed, velocity gradient and mixing time. In the result, the optimum condition was at pH 9.0, Mg2+ : PO43- : NH4+ = 1.5 : 1.5 : 1.0. When seed was injected at landfill leachate, the removal efficiency of injecting wet seed was higher than injecting dry seed. However, It was concluded that the mixing time and the velocity gradient were not significant factor on the struvite crystallization. KCI Citation Count: 0